PENGARUH PROFITABILITAS, PERSISTENSI LABA, STRUKTUR MODAL, DAN RISIKO SISTEMATIK TERHADAP EARNINGS RESPONSE COEFFICIENT (ERC) - Silviana Fauziah, 13.05.52.0120; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
The purpose of this research is to influence profitability, profit persistence, capital structure, and systematic risk to earnings response coefficient at manufacturing companies listed in Indonesia Stock Exchange year 2013-2015. The population is all manufacturing companies listed on the BEI in 2013-2015.The sampling method using purposive sampling. The total sample is 50 data. Total observations during 2013-2015 150 data. Data analysis was done by classical assumption test and hypothesis test by multiple linear regression method. The results of the analysis can be concluded that: Profitability has positive and not significant effect on earning response coefficient. Profit persistence positively affects earnings response coefficient. Capital structure has positive and insignificant effect on earning response coefficient. Systematic risk positively affects earnings response coefficient.Keywords: Profitability, Profit Persistence, Capital Structure, and Systematic Risk to Earnings Response Coefficient